NEGOTIATING GRAMMAR INSTRUCTION IN NON-FORMAL EFL SETTING: A NARRATIVE INQUIRY INTO INDONESIAN TEACHERS’ LIVED EXPERIENCES - Nazarudin Manik; Farida Repelita Waty Kembaren; Utami Dewi (Universitas Muhammadiyah Makassar, 2026)
Grammar instruction remains a central yet contested component of English language teaching (ELT), particularly in non-formal EFL settings where pedagogical flexibility often intersects with institutional and commercial demands. Despite the rapid growth of non-formal English education in Indonesia, limited research has examined how grammar instruction is interpreted, negotiated, and practiced in decentralized learning environments. Addressing this gap, the present study aims to explore how English teachers at the Accelerated English Centre (AEC) Medan conceptualize and negotiate grammar instruction within a non-formal institutional context. The novelty of this study lies in its focus on grammar pedagogy in privately managed EFL institutions, an area that remains underrepresented in mainstream ELT research dominated by formal school settings. Anchored in a narrative inquiry framework within a constructivis-interpretivist paradigm, this qualitative study involved five English teachers and five students selected through purposive sampling. Data were collected through semi-structured interviews, classroom observations, and document analysis, and were analyzed using thematic and narrative analysis. The findings revealed four interrelated themes: the dominance of explicit grammar instruction, the integration of grammar with communicative tasks, tensions between pedagogical ideals and institutional expectations, and adaptive instructional strategies shaped by learner needs and classroom realities. The findings demonstrate that grammar instruction in non-formal EFL settings is not merely the transmission of grammatical rules, but a dynamic and context-sensitive process shaped by teacher agency, learner expectations, and institutional pressures. The study contributes theoretically by extending Focus on Form (FonF), postmethod pedagogy, and constructivist perspectives into underexplored non-formal educational spaces. Practically, it highlights the importance of adaptive professional development and flexible instructional design in supporting effective grammar pedagogy in emerging EFL sectors. Overall, this research underscores the need to recognize local teaching ecologies and contextual realities in shaping grammar instruction within contemporary English language education.